Early-onset Parkinson's disease: An assessment of unmet psychosocial needs. (May 2023) - McDaniels, Bradley; Subramanian, Indu; Kurian, Shelley; Chitnis, Shilpa
Abstract: Background: Early onset Parkinson's disease (EOPD) affects people in the prime of their lives, typically between 21 and 50 years of age, which results in a variety of challenges that are unique compared to those diagnosed later in life. A better understanding of the unmet needs of this population is critical to delivering bespoke care and improving their quality of life. Objectives: To assess the unmet needs of people with early onset Parkinson's disease. Methods: A cross-sectional sample of 198 adults with self-identified early onset Parkinson's disease completed surveys to ascertain the most common unmet needs of this population. Simple descriptive statistics including frequencies, means, and standard deviations were used to quantify the most common unmet needs and were compared between men, women, and Hispanic/Latino with significance determined by chi-square tests. Results: Overall, the top five unmet needs were (1) need for "a community more like me" (65.2%), (2) more PD information (48%), (3) information about how their PD will progress (47%), (4) help with mental health issues (34.8%), and (5) help with employment issues (33.8%). The top unmet need for men was help with employment issues (50.8%), for women, "a community more like me" (72.3%), and for Hispanic/Latinos, more PD information (47%). Conclusion: Although the number of people living with EOPD is considerably smaller than those with conventional age at onset, the potential impact to quality of life in this population remains tremendous. We propose a framework to start to address these needs. Highlights: First known study to assess the unique needs of people with EOPD. Number one need was for a "community more like me" (65.2%). Most cited need in men was help with employment issues (50.5%, p = .001). Most cited need in women was "community more like me" (72.3%, p = .001). Unusual number of Hispanic respondents who reported wanting more PD information (47%).